Behavior Transformation during The Covid-19 Pandemic in the Malakok Community of Minangkabau (MUHARRIK: Jurnal Dakwah dan Sosial, 2021)
The study aims to analyze the form of behavioral transformation during the Covid-19 pandemic among the "Malakok" community in Minangkabau, especially in Nagari Sungai Sirah, Pesisir Selatan Silaut District. At this time, almost the entire order of people's lives has changed, including the personal interactions of the community and the social interactions of the transmigration community who do malakok in Nagari Sungai Sirah. The presence of the transmigration community in the Sungai Sirah area resulted in a cultural cross between the Minang community and the transmigrant community to create a diverse society. Meanwhile, the impact of the Covid-19 pandemic on the multicultural society created by this cross-culture has resulted in visible changes, both in daily behavior and social behavior in society. For that, it takes a big heart to adapt to the current situation so that the stability of life in Nagari Sungai Sirah remains stable. This research was conducted using a qualitative phenomenological approach. Collecting data using observation techniques, in-depth interviews and holding a Focus Group Discussion (FGD) at the research site. The results showed that the form of behavioral transformation during the Covid-19 pandemic among the Malakok community was natural, both in terms of personal behavior and social behavior changes. However, they were able to adapt to the new everyday life which had become government policy. The implementation of customs in the mutual village also changed before the occurrence with the period after the Covid-19 pandemic. Previously, all traditional elements required all familiar elements to carry out a custom determined by custom. However, during the Covid-19 pandemic, all traditional elements gave and were given tolerance and relief in implementing the custom. Through the Malakok tradition, immigrant communities can still live side by side and maintain social harmony within the brotherhood framed in an attitude of tolerance and open-mindedness.